ANALISIS PENENTUAN SEKTOR EKONOMI UNGGULAN DI KABUPETEN SUMBAWA - S Suprianto; Sahoda Kirana (Jurnal Ekonomi & Bisnis, 2025)
This study aims to know the leading sectors of Sumbawa district. The type of this study was descriptive study. The sources of data used in this study were primary and secondary data. Primary data in this study was obtained from the results of a questionnaire, while secondary data was GRDP data obtained from the Central Bureau of Statistics (BPS) of Sumbawa District. The tools used to collect data were questionnaires and documentation. The number of respondents in this study were was 9 respondents consisted of bureaucrats and academic experts. Data analysis tools used were Location Quontient (LQ) Analysis, Shift Share Analysis and Analytical Hierarchy Process (AHP). The results of the LQ analysis show that there are 8 leading basic economic sectors in Sumbawa District, namely the agriculture, forestry, and fisheries sector; electricity and gas trade; construction; wholesale and retail trade, car and motorcycle repair; financial and insurance services; government administration and compulsory social security; and education services. The shift share analysis results indicate that nine economic sectors in Sumbawa District had a positive competitive advantages, namely the agriculture, forestry, and fisheries sector; the processing industry; electricity and gas trade; wholesale and retail trade, car and motorcycle repair; transportation and warehousing; provision of accommodation and food and beverage; corporate services; health services and social activities; and other services. Meanwhile, the results of the superior weight calculation using AHP analysis show that the agriculture, forestry and fisheries sectors obtained the highest value, making them the leading economic sectors in Sumbawa District.